Are Judges Listening? Rethinking Sentencing in Child Sexual Violence through Victim Impact Statements in Indonesia - Anang Riyan Ramadianto; Milda Istiqomah; Nurini Aprilianda (Faculty of Law Universitas Jenderal Soedirman, 2025)
The protection of victims' rights, especially child victims of sexual violence, remains a major challenge in Indonesia's criminal justice system. One critical yet underutilized instrument is the Victim Impact Statement (VIS), which allows victims to convey the psychological, emotional, social, and economic impact of the crime they experienced. However, the implementation of VIS in Indonesia is still limited due to the absence of explicit regulation in the current Criminal Procedure Code (KUHAP). This paper aims to examine the role of VIS in strengthening victim protection and to analyze the inhibiting factors affecting its implementation in the Karanganyar District Court. Using a socio-legal approach, this study combines normative legal research with empirical data gathered through interviews with judicial actors. The findings reveal that the main obstacles lie in three areas: the lack of legal substance (absence of specific VIS regulation), weak legal structure (limited procedural guidelines and institutional support), and unsupportive legal culture (stigmatization of victims and lack of victim-centered perspectives among legal practitioners). The study proposes a structured model of VIS based on Supreme Court Regulation No. 1 of 2022 and international practices, aiming to fill the normative gap and support future reform of Indonesia’s criminal procedure law. Strengthening VIS as a legal and procedural tool is essential for ensuring justice that is not only punitive but also restorative and responsive to the needs of victims.